2012
DOI: 10.4082/kjfm.2012.33.6.390
|View full text |Cite
|
Sign up to set email alerts
|

Marital Status and Health Behavior in Middle-aged Korean Adults

Abstract: BackgroundMarital status is as an important sociodemographic variable for health studies. We assessed the association between marital status and health behavior in middle-aged Korean adults.MethodsThis is a cross-sectional study of 2,522 Korean middle-aged adults (1,049 men, 1,473 women) from the 2010 Korean National Health and Nutrition Examination Survey. The subjects were classified as living with a partner or living without a partner (never married, separated, widowed, and divorced). We assessed the relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
18
2
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 25 publications
5
18
2
2
Order By: Relevance
“…Part of the reasons why widows have increased mortality was due to having more risk factors and comorbidities. In this cohort, as in other studies, widows had more smoking,[ 32 33 ] drinking,[ 32 34 ] obesity,[ 33 35 36 ] sleep problems,[ 34 37 ] hypertension, [38] and reduced their physical activity [39] than married women. Either singly or in combination, these risks or comorbidities contributed to poorer health of the widows.…”
Section: Discussionsupporting
confidence: 80%
“…Part of the reasons why widows have increased mortality was due to having more risk factors and comorbidities. In this cohort, as in other studies, widows had more smoking,[ 32 33 ] drinking,[ 32 34 ] obesity,[ 33 35 36 ] sleep problems,[ 34 37 ] hypertension, [38] and reduced their physical activity [39] than married women. Either singly or in combination, these risks or comorbidities contributed to poorer health of the widows.…”
Section: Discussionsupporting
confidence: 80%
“…For example, they may not need to take care of their partners. A study also found that living without partners may increase the risk of smoking and alcohol consumption, having irregular breakfast and prevent them from undergoing health screening 45 .…”
Section: Discussionmentioning
confidence: 99%
“…Nonmarried persons have a different lifestyle than those who are married. For example, nonmarried individuals have a higher risk of alcohol consumption and are less likely to eat breakfast regularly [41]. Nonmarried persons also have less cognitive stimulation due to a small social network and fewer leisure activities.…”
Section: Discussionmentioning
confidence: 99%